Statistical Inference Approaches for Investigating Gene Frequencies in Biometric Research (International Journal of Food and Nutritional Sciences, 2021)
This research paper delves into the application of statistical inferential methods to estimate gene frequencies in the context of biometric research. Gene frequencies are pivotal in understanding genetic variation within populations and hold profound implications for various fields, including genetics, epidemiology, and evolutionary biology. Leveraging statistical inference techniques, we present a comprehensive methodology for accurate gene frequency estimation.